The Effect of Demonstration Learning Method on Students' Learning Outcomes - Niati, Dini; Anita, Tri; Wasahua, Olos (Candradimuka: Journal of Education, 2025)
This research aims to determine if there is an influence of the demonstration learning method on the learning outcomes of students in class XI SMA Negeri 104 Jakarta. This research was conducted using quantitative methods with descriptive formulations. The population in this study was class XI students with a total of 285 students with a sample size of 74 using random sampling techniques. The data collection method in this research uses a questionnaire with a total of 30 questions and each variable has 15 statements. Through the calculation of rxy 0.227, which means that there is sufficient influence between the demonstration method on student learning outcomes in class XI PKWU subjects at SMAN 104 Jakarta. Based on the results of the coefficient of determination analysis, the contribution of variable X is 0.51% and the remaining 49% is the contribution of other factors not examined in this research. This influence has been tested using regression hypothesis testing (influence), where tcount is greater than ttable namely 5.027 > 1.993. This shows that there is an influence between the demonstration method on student learning outcomes.